2020
DOI: 10.1111/jmg.12552
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative elemental mapping of granulite‐facies monazite: Textural insights and implications for petrochronology

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In Canada, numerous studies of the Trans-Hudson orogen have shown that it formed during progressive closure of the Manikewan Ocean and accretion of intervening suspect terranes, culminating with the collision of the lowerplate Archean Superior craton with an upper-plate collage of Archean and Paleoproterozoic crustal blocks (collectively known as the Churchill plate) at ca. 1.82 Ga (St-Onge et al, 2006Corrigan et al, 2009;Corrigan, 2012;Weller and St-Onge, 2017;Weller et al, 2020; and references therein). Several parallels have been drawn between the Trans-Hudson orogen and the archetypical Himalaya-Tibet orogen of central Asia as both orogens are of a similar scale and exhibit similar patterns of magmatism and metamorphism with respect to the timing of collision (St-Onge et al, 2006;Eaton and Darbyshire, 2010;Thompson et al, 2010;Bastow et al, 2011;Corrigan, 2012;Weller and St-Onge, 2017).…”
Section: Trans-hudson Orogeny and Closure Of The Manikewan Oceanmentioning
confidence: 99%
“…In Canada, numerous studies of the Trans-Hudson orogen have shown that it formed during progressive closure of the Manikewan Ocean and accretion of intervening suspect terranes, culminating with the collision of the lowerplate Archean Superior craton with an upper-plate collage of Archean and Paleoproterozoic crustal blocks (collectively known as the Churchill plate) at ca. 1.82 Ga (St-Onge et al, 2006Corrigan et al, 2009;Corrigan, 2012;Weller and St-Onge, 2017;Weller et al, 2020; and references therein). Several parallels have been drawn between the Trans-Hudson orogen and the archetypical Himalaya-Tibet orogen of central Asia as both orogens are of a similar scale and exhibit similar patterns of magmatism and metamorphism with respect to the timing of collision (St-Onge et al, 2006;Eaton and Darbyshire, 2010;Thompson et al, 2010;Bastow et al, 2011;Corrigan, 2012;Weller and St-Onge, 2017).…”
Section: Trans-hudson Orogeny and Closure Of The Manikewan Oceanmentioning
confidence: 99%
“…as done by McKenzie & Priestley, 2016). This approach is taken because of recent results suggesting that partial melting has a limited effect on the rates of radiogenic heating in the partitioned melt and residue, due to the growth and/or retention of relatively high‐Th accessory minerals in the residue compensating for the removal of other heat‐producing elements during anatexis and melt migration (Alessio et al., 2018; Weller et al., 2020; Yakymchuk & Brown, 2019). This result is consistent with the lack of observed correlation between metamorphic grade and rate of radiogenic heating in global compilations (Hasterok et al., 2018).…”
Section: Model Set‐upmentioning
confidence: 99%
“…Rudnick & Gao, 2014; Hacker et al., 2015). It is an open question how to reconcile these models and the observations of limited differences in radiogenic heating between sub‐ and supra‐solidus rocks (Alessio et al., 2018; Bea & Montero, 1999; Weller et al., 2020; Yakymchuk & Brown, 2019). We therefore take the simple approach of assuming constant radiogenic heating throughout the crust.…”
Section: Model Set‐upmentioning
confidence: 99%
“…This is consistent with a low modal abundance of garnet (<<5%) that is highly resorbed and embayed by matrix biotite grains hosting most monazite inclusions (Figure 3a). Alternatively, a recent study by Weller et al (2020) shows that the trace element content of monazite may reflect local equilibria independent of microstructural location or proximity to garnet.…”
Section: Timing Of Metamorphism In the Egcmentioning
confidence: 99%